1985
DOI: 10.2307/3430042
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks from Acid Rain: A Canadian Perspective

Abstract: Acidic deposition, commonly referred to as acid rain, is causing serious environmental damage in eastern Canada. The revenues from forest products, tourism and sport fishing are estimated to account for about 8% of the gross national product. The impact on human health is not as clearcut and a multi-department program on the Long-Range Transport of Airborne Pollutants (LRTAP) was approved by the federal government in June 1980. The objectives of the LRTAP program are to reduce wet sulfate deposition to less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…An optimal taste was found at 270 and 90 mg/L for calcium sulphate and magnesium sulphate, respectively (Zoeteman, 1980). Sulphate concentrations in rain water in Canada varied between 1.0 and 3.8 mg/L in 1980 (Franklin, 1985). An annual mean value of about 6 mg/L in precipitation over central Europe has been reported .…”
Section: Sulphatesmentioning
confidence: 99%
“…An optimal taste was found at 270 and 90 mg/L for calcium sulphate and magnesium sulphate, respectively (Zoeteman, 1980). Sulphate concentrations in rain water in Canada varied between 1.0 and 3.8 mg/L in 1980 (Franklin, 1985). An annual mean value of about 6 mg/L in precipitation over central Europe has been reported .…”
Section: Sulphatesmentioning
confidence: 99%
“…Troedsson reported that although pH changes in forest soils were slight, marked losses of exchangeable Ca, Mg, and K had occurred, presumably due to acid rain (2). Troedsson have also failed to statistically prove a relationship between acid rain and human health, although trends of detrimental effects were apparent (4). Few studies have considered radiological effects on man that may result from acid rain.…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, las concentraciones de sulfato en lluvia oscilaban entre 1,0 y 3,8 mg/L en 1980 [6]; se ha notificado un valor medio anual de alrededor de 6 mg/L de precipitación sobre Europa central [7]. Los niveles de sulfato en agua de lluvia y agua superficial se correlacionan con las emisiones de dióxido de azufre ocasionadas por la actividad humana [8], principalmente provenientes de motores que utilizan como combustible diésel.…”
Section: Ion Sulfatounclassified